WHEN THE SOURCE OF LIFE BECOMES A COMMODITY - Sasi, K. P (Journal of Dharma, 2006)
“In the beginning there was just water... All this world is woven, warp and woof on water” (Upanisad). “We made from water every living thing” (Koran, 21:30). “For my people have committed two evils; they have forsaken me the fountain of living waters, and hewed them out cisterns, broken cisterns, that can hold no water” (Jeremiah 2:13). All religions had an inherent respect for water. Apart from the organised religions, indigenous systems of faith recognised water as a spiritual entity. Water bodies were worshiped. In India, the Ganges, the Yamuna, the Brahmaputra, and most of the rivers were worshipped as Goddesses. Water is the source of all life. All life on earth can move only if there is water within them. Most of human body as well as of all other species consist of water. “There is no life possible without water. Water is a part and parcel of the living machinery,” said the discoverer of vitamin C, Alber Szent-Gyorgi. Yet, water is one of the most threatened entities on the earth. The rivers, lakes, wells, ponds, and even ground water are dying. Modern development saw water as a mere object to be used as a resource for commodity production. With globalisation, the status of water transcended from a resource for commodity production to a commodity in itself.